Sekolah Alam untuk Anak Usia Pra-Sekolah di Kampar Dengan Pendekatan Arsitektur Rumah Lontik - W.U, Natalia Dwiyanti; Hidayat, Wahyu; Faisal, Gun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Kampar has a natural potential that can be developed into a natural school. School of nature is a method of education by using the condition of the environment is still natural as a medium of learning. Golden Age is a time when almost all of the potential of children experiencing rapid development, so that the education of pre-school children such as early childhood and kindergarten. Applying the natural school method will develop the potential of the child better, make the child become love with the environment, can play freely and learn to socialize. The use of Lontik House Theme as a reference design on the building, the application of the meaning of the home part of the lontik as the order of the period of building and the division of zoning area. Lontik House is a traditional Kampar building with an interesting shape. The concept of Natural Exploration, by utilizing the natural potential that is in tepak so as to produce the order of the region in accordance with the functions and needs of the School of Nature without changing too many natural conditions.Keywords: Kampar, Lontiok House, School of Nature